Cover Image. Issue 2 (14th March 2019) - Marais, Ben J.; Buddle, Bryce M.; de Klerk‐Lorist, Lin‐Mari; Nguipdop‐Djomo, Patrick; Quinn, Frederick; Greenblatt, Charles
Abstract : The cover image is based on the Short Communication BCG vaccination for bovine tuberculosis; conclusions from the Jerusalem One Health workshop, by Ben J. Marais et al., DOI 10.1111/tbed.13089 .